1999
DOI: 10.1074/jbc.274.20.13915
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Role of Group VI Phospholipase A2 in Fatty Acid Incorporation, Phospholipid Remodeling, Lysophosphatidylcholine Generation, and Secretagogue-induced Arachidonic Acid Release in Pancreatic Islets and Insulinoma Cells

Abstract: H]arachidonate was initially incorporated or its subsequent transfer from PC to other lipids. Electrospray ionization mass spectrometric measurements indicated that inhibition of INS-1 cell iPLA 2 accelerated arachidonate incorporation into PC and that inhibition of islet iPLA 2 reduced LPC levels by 25%, suggesting that LPC mass does not limit arachidonate incorporation into islet PC. Gas chromatography/mass spectrometry measurements indicated that BEL but not propranolol suppressed insulin secretagogue-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
122
1
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(140 citation statements)
references
References 89 publications
15
122
1
2
Order By: Relevance
“…Besides cPLA 2 , the other PLA 2 that is present in many cell types and involved in agonist-induced arachidonic acid release is the most recently characterized one, iPLA 2 (21-23). One of the major functions attributed to iPLA 2 is its role in lipid remodeling (39,40). In fact, using its selective inhibitors such as BEL, it was shown that arachidonic acid release in response to some agonists is mediated primarily by iPLA 2 (23).…”
Section: Resultsmentioning
confidence: 99%
“…Besides cPLA 2 , the other PLA 2 that is present in many cell types and involved in agonist-induced arachidonic acid release is the most recently characterized one, iPLA 2 (21-23). One of the major functions attributed to iPLA 2 is its role in lipid remodeling (39,40). In fact, using its selective inhibitors such as BEL, it was shown that arachidonic acid release in response to some agonists is mediated primarily by iPLA 2 (23).…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that muscarinic receptor occupancy increases ␤-cell Kv current inactivation by iPLA 2 ␤-regulated mechanism(s), and this results in a shorter time to peak Kv current response. Phospholipase A 2 Regulates Delayed Rectifier Current Activity-iPLA 2 ␤ is expressed by islet ␤-cells from rats (29), humans (47), and mice (48), and by several insulinoma cell lines (31,38,39). Upon activation, iPLA 2 ␤ hydrolyzes the sn-2 substituent from phospholipids substrates, such as phosphatidylcholine, to yield a free fatty acid and a lysophospholipid, such as LPC (44,54,55).…”
Section: Resultsmentioning
confidence: 99%
“…The phospholipid content of esterified AA is higher in pancreatic islets than in other tissues (23,25,26,29), and arachidonate is hydrolyzed from phospholipids upon stimulation of islets with secretagogues (13,14,27,31,36,44) and accumulates to micromolar concentrations (7,27,28) that are sufficient to modulate delayed rectifier Kv channel FIGURE 5. Effects of the muscarinic agonist carbachol on INS-1 cell-delayed rectifier currents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations